2015
DOI: 10.5604/17322693.1164409
|View full text |Cite
|
Sign up to set email alerts
|

Selected endothelial hemostatic markers in patients with peripheral arterial disease after endovascular revascularization and restenosis formation

Abstract: Surgical and endovascular revascularization of ischemic legs in patients with peripheral arterial disease (PAD) can damage the arterial wall (endothelial and smooth muscle cells). Hemostatic factors released during endothelial dysfunction can lead to restenosis. 1. Determination of selected endothelial hemostatic factors in PAD patients and a reference group. 2. Prospective observation of new restenosis appearance in PAD patients after endovascular revascularization. 3. Comparison of selected endothelial hemos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 0 publications
1
9
1
1
Order By: Relevance
“…Many articles exist on this theme. We also observed, in PAD patients after endovascular revascularization and in patients with restenosis increased inflammatory factors: CRP, fibrinogen and interleukin 6 and 10 [14]. The mean or median levels of TF, TAT complexes, fibrinogen and D-dimers in PAD patients after endovascular revascularization were significant higher than in the younger reference group (Table 2).…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Many articles exist on this theme. We also observed, in PAD patients after endovascular revascularization and in patients with restenosis increased inflammatory factors: CRP, fibrinogen and interleukin 6 and 10 [14]. The mean or median levels of TF, TAT complexes, fibrinogen and D-dimers in PAD patients after endovascular revascularization were significant higher than in the younger reference group (Table 2).…”
Section: Discussionsupporting
confidence: 56%
“…In our patients, higher fibrinogen level is not only a clotting factor, but also an inflammatory mediator. In group A of the patients, the mean level of CRP was 4.35 mg/L [14]. Schillinger et al suggested that CRP better predicts the inflammatory process than fibrinogen [18].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Next finding of our study is that vasodilation indices (relative changes in temperature oscillations during local heating) in the endothelial range are well correlated with the laboratory markers of ED: endothelin, homocysteine, and vWF. Increased vWF levels in PAD patients indicate arterial endothelial cell damage by atherosclerotic and revascularization processes . We have found that, as the disease progresses, the levels of endothelin and vWF increase and are negatively correlated with the vasodilation index in the endothelial frequency range.…”
Section: Discussionmentioning
confidence: 81%
“…Some substances are considered potential laboratory markers of ED, such as tissue plasminogen activator and its inhibitor, thrombomodulin, homocysteine, vWF, and endothelin . Noninvasive explorations of cutaneous microcirculation based on the laser Doppler and temperature measurement techniques are widespread in the field of microvascular function research , but no studies have yet explored the relationship between multiple laboratory markers of ED and cutaneous blood flow parameters, particularly the characteristics of ST oscillations.…”
Section: Introductionmentioning
confidence: 99%